1992
DOI: 10.1111/j.1471-6712.1992.tb00133.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Responsible for Patients' Falls

Abstract: The study determined intrinsic factors which contributed to the falls of adults hospitalized in a general hospital during 1987-88. Two hundred and fourteen patients were studied in two groups. Group A consisted of 108 patients who fell during their hospitalization and control Group B consisted of 106 patients with the same characteristics also hospitalized during the same period who did not fall. Of the 23 variables which have been analyzed by the multivariate logistic regression method, seven present statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
28
0
4

Year Published

1996
1996
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 24 publications
6
28
0
4
Order By: Relevance
“…Velde et al [13] reported that by decreasing or stopping hypnotics, which are thought to be one of the FRID, they morning [8][9][10]. The hypnotic effects that are seen when excreting at night or early in the morning may affect falls.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Velde et al [13] reported that by decreasing or stopping hypnotics, which are thought to be one of the FRID, they morning [8][9][10]. The hypnotic effects that are seen when excreting at night or early in the morning may affect falls.…”
Section: Discussionmentioning
confidence: 95%
“…The association between the use of benzodiazepine (BZ) hypnotics in older adults and the risk of hip fracture is well established [4][5][6][7]. Quite a few fall events occur in the bedroom and the toilet/bathroom during the night or early morning [8][9][10]. However, there are other reports that the insomnia itself is more related to those accidents rather than the use of hypnotics [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Falls are one of the most common complications of many neurological diseases such as stroke, multiple sclerosis, and Parkinson's (Soyuer, Soyuer, & € Ozt€ urk, 2006). It is indicated that postoperative stage caused falls (Plati, 1992;Berke & Eti, 2010). Nurses in this study described patient falls in units as most common during transfer, mobilization, sitting in a chair, or a bath.…”
Section: Discussionmentioning
confidence: 98%
“…Many studies have been conducted to identify the risk of patient falls and to develop certain standards to prevent them (Fischer et al, 2005;Hendrich et al, 2003;Houghton, Birks, Whitehead, & Crotty, 2004;Plati, Lanara, & Mantas, 1992;Rabadi, Rabadi, & Peterson, 2008). In a study conducted by Savci et al (2007) on the incidents of patient falls in units in Turkey, it was found that 53.7% of the patients in the study sample were at high risk of falling (Savcı et al, 2009).…”
Section: Introductionmentioning
confidence: 94%
“…Anaemia, which is almost universal in ESRD, is an independent risk factor for falls in the general population [15]. Multifactorial myopathy [16], vitamin D insufficiency [17,18], polypharmacy [19] and depression [20,21] are other accepted falls risk factors which are particularly common in the dialysis population.…”
Section: Introductionmentioning
confidence: 99%